2009
DOI: 10.1063/1.3099947
|View full text |Cite
|
Sign up to set email alerts
|

Transient photovoltaic behavior of air-stable, inverted organic solar cells with solution-processed electron transport layer

Abstract: The short-circuit current density of inverted organic solar cells comprising a solution-processed titania electron transport layer increases with continuous illumination in air and saturates after 10 min. On extended exposure (>2 days), the open-circuit voltage of the devices increases also. The improvement in device characteristics over short time scales is attributed to the filling of shallow electron traps in titania. With an increase in photoconductivity of titania, the short-circuit current increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(129 citation statements)
references
References 21 publications
1
128
0
Order By: Relevance
“…The photocurrent continuously increases with an increase in the irradiation time and this corresponds to a decrease in both R1 and R2. Kim et al 26 reported that the emergence of photoconduction of titanium oxide films mirrored the increase and gradual saturation of the photocurrent of TiO x cells. This may be supported by the decrease in R1.…”
Section: -1 Characteristics Of the Inverted Polymer Solar Cells Upomentioning
confidence: 99%
“…The photocurrent continuously increases with an increase in the irradiation time and this corresponds to a decrease in both R1 and R2. Kim et al 26 reported that the emergence of photoconduction of titanium oxide films mirrored the increase and gradual saturation of the photocurrent of TiO x cells. This may be supported by the decrease in R1.…”
Section: -1 Characteristics Of the Inverted Polymer Solar Cells Upomentioning
confidence: 99%
“…Both of these are detrimental to the device lifetime of BHJ PSCs. [8][9][10] The rapid advancement in the PCE of PSCs, means that the poor stability of PSCs is becoming one of the crucial obstacles to commercialization. One approach to solve this issue is using an inverted structure in which the charge separation and collection nature of the electrode are reversed.…”
Section: Introductionmentioning
confidence: 99%
“…Mostly the open-circuit voltage (V oc ) or the fill factor (FF) are negatively affected. The low FF often comes along with distorted current-voltage (J-V ) curves in the extreme case showing inflection points close to V oc (so-called S-kink) [6,7,8,9].…”
mentioning
confidence: 99%